2014
DOI: 10.2147/ijn.s62972
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanostructured TiO2 crystal phase on photoinduced apoptosis of breast cancer epithelial cells

Abstract: PurposeThe use of nanoparticles has seen exponential growth in the area of health care, due to the unique physicochemical properties of nanomaterials that make them desirable for medical applications. The aim of this study was to examine the effects of crystal phase-nanostructured titanium dioxide particles on bioactivity/cytotoxicity in breast cancer epithelial cells.Materials and methodsCultured Michigan Cancer Foundation (MCF)-7 and human breast adenocarcinoma (MDA-MB-468) breast cancer epithelial cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 60 publications
1
14
0
1
Order By: Relevance
“…These electron-hole pairs, generated after the introduction of TiO 2 into living tissues or cells, can react with surrounding oxygen to form various ROS such as H 2 O 2 , • OH, or O 2 •− 87, 88 . The effective production of ROS by TiO 2 NPs is the main contributing factor in its successful use as cytotoxic reagents in human cervical adenocarcinoma, 89 hepatocarcinoma, 90 non-small cell lung cancer, 91 breast cancer, 92 and leukemia 93 cell lines. In an early study, Cai et al 89 demonstrated the ROS generating capability (as well as the potential for tumor tissue penetration) of TiO 2 NPs as they found that 10 min UV irradiation of TiO 2 particles at 50 μg mL −1 was sufficient for complete HeLa cell death.…”
Section: Titanium Oxide Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…These electron-hole pairs, generated after the introduction of TiO 2 into living tissues or cells, can react with surrounding oxygen to form various ROS such as H 2 O 2 , • OH, or O 2 •− 87, 88 . The effective production of ROS by TiO 2 NPs is the main contributing factor in its successful use as cytotoxic reagents in human cervical adenocarcinoma, 89 hepatocarcinoma, 90 non-small cell lung cancer, 91 breast cancer, 92 and leukemia 93 cell lines. In an early study, Cai et al 89 demonstrated the ROS generating capability (as well as the potential for tumor tissue penetration) of TiO 2 NPs as they found that 10 min UV irradiation of TiO 2 particles at 50 μg mL −1 was sufficient for complete HeLa cell death.…”
Section: Titanium Oxide Nanomaterialsmentioning
confidence: 99%
“…While toxic effects are not ideal in the field of nanotechnology, exploitation of the photocatalytic properties of TiO 2 led to the demonstration of TiO 2 -mediated cytotoxicity in cancer research. Lagopati et al 92 investigated the feasibility of employing TiO 2 as an anticancer agent in the presence of ultraviolet light. They hypothesized that crystallinity would impact oxidant generation, and therefore explored the effect of the particle crystal phase of TiO 2 dispersions using two breast epithelium cancer cell lines: MDA-MB-468 and MCF-7.…”
Section: Titanium Oxide Nanomaterialsmentioning
confidence: 99%
“…Light induced ROS generation by a photosensitizer has been applied in treatment of several diseases called PDT 21 , 22 . Potential of TiO 2 NPs to be applied in PDT for different types of cancers, such as leukemia, cervical, liver and lung cancers is already reported 23 , 24 . Still, there are some drawbacks in the application of TiO 2 NPs for PDT.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of PDT compared to other anti-cancer strategies include the lack of known drug resistance and the ability to control ROS production in cancer cells by controlling PDT doses 6 7 8 . The successful use of TiO 2 NPs in PDT has been reported for many different types of cancers, such as human cervical adenocarcinoma, hepatocarcinoma, non-small cell lung cancer, and leukemia 5 9 10 11 12 . However, the biggest obstacle in the clinical application of TiO 2 -based NPs for PDT is the TiO 2 high band-gap energy level (3.2 ev for anatase) that requires excitation with harmful UV radiation (λ < 387 nm) 4 13 14 15 .…”
mentioning
confidence: 99%